Mechanical Drawing / 8th Edition - French Thomas; Helsen Jay D; Svensen Carl L; Urbanick Ryron (Mcgraw Hill Book Company, 1974)
Twentieth Century Drafting, Sketching, The Use and Care of Drafting Equipment, Geometry for Technical Drawing, Dimensioning, Auxiliary Views and Revolutions, Basic Descriptive Geometry, Sectional Views and Conventions, Fasteners, Working Drawings, Pictioral Drawing, Inking, Drafting Media and Reproduction, Systems for Graphic Communications, Functional Reading, Welding Drafting, Surface Developments and Intersections, Cams and Gears, Architectural Drafting, Structural Drafting, Map Drafting, Graphic Charts and Diagrams, Electrical and Electronic Drafting, Aerospace Drafting, Technical Illustration, Appendixes, Index.